Effect of Breastfeeding Technique Education on Breastfeeding Success Among Primiparous Postpartum Mothers in Magetan - Nunung Devi M; Nurlailis Saadah; Astuti Setiyani; Budi Joko Santosa (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Exclusive breastfeeding rates in Indonesia remain below national and global targets, with a substantial proportion of postpartum mothers experiencing breastfeeding difficulties, particularly among primiparous women. Inadequate breastfeeding technique is a major contributing factor, often resulting from limited experience, insufficient education, and lack of hands-on guidance during the early postpartum period. These challenges may compromise breastfeeding success, maternal confidence, and infant nutrition outcomes. This study aimed to examine the effect of structured breastfeeding technique education on breastfeeding success among primiparous postpartum mothers. A quantitative pre-experimental study with a onegroup pretest–posttest design was conducted at RSUD dr. Sayidiman Magetan. Forty primiparous postpartum mothers were recruited using non-probability sampling based on predefined inclusion criteria. The intervention consisted of structured breastfeeding technique education delivered by trained midwives through direct explanation, visual leaflets, practical demonstrations, and interactive discussion sessions. Breastfeeding success was assessed before and after the intervention using the LATCH scoring system, which evaluates latch, audible swallowing, nipple type, maternal comfort, and infant positioning. Data were analyzed using the Wilcoxon Signed-Rank Test. The results demonstrated a statistically significant improvement in breastfeeding success following the educational intervention (Z = −5.35, p < 0.005), with a large effect size (r = 0.85). Prior to education, 75% of mothers were classified in the “not successful” category, while none achieved a “good” score. After the intervention, 70% of participants attained good breastfeeding success, and the proportion of mothers with inadequate scores decreased to 2.5%. Improvements were consistently observed across all LATCH components. In conclusion, structured breastfeeding technique education significantly enhances breastfeeding success among primiparous postpartum mothers. Integrating systematic, hands-on breastfeeding education into routine postnatal care is strongly recommended to promote effective breastfeeding practices and support exclusive breastfeeding goals.